2019
DOI: 10.1002/lio2.333
|View full text |Cite
|
Sign up to set email alerts
|

A visual analog scale for patient‐reported voice outcomes: The VAS voice

Abstract: Objectives Although patient‐reported outcome measures (PROMs) can be useful for assessing quality of life, they can be complex and cognitively burdensome. In this study, we prospectively evaluated a simple patient‐reported voice assessment measure on a visual analog scale (VAS voice) and compared it with the Voice Handicap Index (VHI‐10). Study design Prospective survey. Methods An abbreviated voice measure was designed by a team of otolaryngologists, speech pathologists, and patients that consisted of four VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
1
13
0
2
Order By: Relevance
“…Con los resultados presentados en este estudio es posible afirmar que existe un vínculo fuerte entre la severidad de la disfonía y la autopercepción de la voz medida a través de cuestionarios de autorreporte. La literatura ha referido que la autopercepción vocal de los pacientes es coherente con la severidad de la disfonía presentada [34,35,37,[39][40][41]44], aspecto que refuerza la importancia de utilizar este tipo de instrumentos en la evaluación de la voz.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Con los resultados presentados en este estudio es posible afirmar que existe un vínculo fuerte entre la severidad de la disfonía y la autopercepción de la voz medida a través de cuestionarios de autorreporte. La literatura ha referido que la autopercepción vocal de los pacientes es coherente con la severidad de la disfonía presentada [34,35,37,[39][40][41]44], aspecto que refuerza la importancia de utilizar este tipo de instrumentos en la evaluación de la voz.…”
Section: Discussionunclassified
“…Por último, es importante medir de manera objetiva la autopercepción vocal de la disfonía por parte del paciente [34,35]. Para ello se han creado diferentes instrumentos de autorreporte [11,[36][37][38][39][40][41][42] que permiten identificar la apreciación del sujeto sobre sus cualidades vocales y el grado de dificultad que observa a la hora de realizar tareas y actividades cotidianas [43][44][45]. Los datos registrados en estas mediciones suelen estar vinculados con el nivel de gravedad de la disfonía [36,37,40,41].…”
Section: Disclaimerunclassified
“…Shortened PROMs may be beneficial in overcoming this barrier. Naunheim et al recently created a shortened, four‐question visual analog scale (VAS) to substitute for the validated PROM, VHI‐10 19 . These authors found that although their four questions attempted to distinguish between physical, functional, and emotional aspects of voice, their “VAS voice” (similar to the VHI‐10) demonstrated only one underlying construct that was being measured.…”
Section: Discussionmentioning
confidence: 99%
“…To compare postoperative follow-up between the two groups, we carefully searched and collected imaging data to evaluate changes in the ankle angle and Takakura stage. Moreover, the pre-and post-operation American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot score [18], ankle range of motion (ROM) [19], and visual analogue scale (VAS) [20] were used to assess functional outcomes.…”
Section: Measurement and Follow-upmentioning
confidence: 99%